Abundance of ants (Hymenoptera: Formicidae) and the functional groups in two different habitats - Ananto Triyogo; Budiadi; Siti Muslimah Widyastuti; Sena Adi Subrata; Suwito Susetyo Budi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Triyogo A, Budiadi, Widyastuti SM, Subrata SA, Budi SS. 2020. Abundance of ants (Hymenoptera: Formicidae) and the functional groups in two different habitats. Biodiversitas 21: 2079-2087. Land development often affects the quantity and diversity of ants (Hymenoptera: Formicidae). The aim of this study, therefore, was to determine and compare the ant species abundance and the functional groups between two different habitats, representing land development, including pioneer and agroforestry. This research involved a survey of the ants at the Forest Research Education (FRE) of Wanagama I Yogyakarta, and data were accumulated over a period of five months (April, May, June, July, and August). In addition, pit-fall trap and direct collection methods were used, involving the placement of 54 pit-fall traps at two habitats, and the ant specimens were retrieved after a two day period. The results show the total individual abundance of 2,310 and 2,067, on agroforestry and pioneer, respectively. Furthermore, the species richness and diversity index was higher in agroforestry (7; 2.01), compared with pioneer (6; 1.49), where the three dominant species include, Anoplolepis gracilipes, Solenopsis sp., Odontoponera denticulata; and Anoplolepis gracilipes, Odontoponera denticulata, Camponotus sp., respectively. Conversely, the highest amount of invasive ants (Solenopsis sp.) was observed in agroforestry, which negatively impacted on the presence of native species (Odontoponera denticulata). In addition, PCA analysis showed the development of three ant groups on each habitat, hence agroforestry made more real differences in the aspect of species abundance, and none in terms of richness. Therefore, notable differences were observed in the ant communities between both habitats, and agroforestry was indicated as a disturbed area, based on the increment in tramp and invasive ants, alongside low abundance of native and functional groups.